Studies of Heterosis in Cashew (Anacardium occidentale L.) - Sethi, Kabita; Lenka, P. C.; Tripathy, P.; Mukherjee, S. K.; Dash, A. K. (International Journal of Bio-resource and Stress Management, 2023)
Cashew (Anacardium occidentale L.) is one of the most important export earning crops of India occupying an area of 9.82 lakh h with a production of 7.28 lakh t. Although India is the largest producer and exporter of cashew in the world, but the productivity is very low, only 722 kg ha-1 as compared to other countries, which is primarily due to seedling progeny of poor genetic stock. Being a highly cross pollinated crop, developing hybrids exhibiting heterosis for important economic characters is one of the ways to enhance the productivity. The present investigation is an attempt to study the extent of heterosis exhibited by certain better promising hybrids which were under taken at All India Coordinated Research Project on Cashew operating under Orissa University of Agriculture and Technology, Bhubaneswar, Odisha, India. The study was conducted to determine the extent of heterosis exhibited by twenty F1 cashew hybrids of ten year old selected plants, based on their superior performance. The results indicated that the hybrid namely A-71, B-27, C-30 and C-41 exhibited better heterosis in terms of nut weight (-0.27 to 19.68%), kernel weight (18.89 to 32.26% ) and overall nut yield (15.51 to 30.70% ) than rest of the tested hybrids. The relative heterosis, heterobeltiosis and standard heterosis among these superior hybrids varied from 85.71 to 94.88%, 57.33 to 65.85% and 15.51 to 30.70%, respectively. Hence, these hybrids may be recommended for cultivation to increase production and productivity of cashew under coastal agro-climatic condition of East coast.